Metal powder manufacturing process using the oxy-acetylene plasma atomization method - Kurniawan, Endang (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2022)
The powder metallurgy process is one of the metalworking technologies by compacting a quantity of powder from pure materials or alloys in a mold, then sintering or heating in a furnace at a certain temperature until bonding occurs between the powder particles. Several advantages of powder metallurgy technology, namely: eliminating or minimizing the machining process, no wasted material, high surface accuracy and smoothness, increased strength and wear resistance, and complex product shapes. Atomization method is a method that is often used to make powders in bulk. Several known atomization methods are the water atomization method, the gas atomization method, and the centrifugal atomization method. Several new methods in the atomization method are the plasma atomization method, liquid explosion atomization method, ultrasonic atomization method, and so on. In this study, molten aluminum metal was used as the starting material, the process used was the oxy-acetylene plasma welding process. The data obtained by testing the distribution of powder, testing the distribution of powder weight, and testing the macro structure of the powder. The powder produced from the oxy-acetylene plasma burst has the characteristics of a non-spherical powder, but is in the shape of a teardrop. This grayish black color is caused by the powder undergoing an oxidation process and a carburizing process. powder weight distribution test, and powder macro structure testing. The powder produced from the oxy-acetylene plasma burst has the characteristics of a non-spherical powder, but is in the shape of a teardrop. This grayish black color is caused by the powder undergoing an oxidation process and a carburizing process. powder weight distribution test, and powder macro structure testing. The powder produced from the oxy-acetylene plasma burst has the characteristics of a non-spherical powder, but is in the shape of a teardrop. This grayish black color is caused by the powder undergoing an oxidation process and a carburizing process.The powder metallurgy process is one of the metalworking technologies by compacting a quantity of powder from pure materials or alloys in a mold, then sintering or heating in a furnace at a certain temperature until bonding occurs between the powder particles. Several advantages of powder metallurgy technology, namely: eliminating or minimizing the machining process, no wasted material, high surface accuracy and smoothness, increased strength and wear resistance, and complex product shapes. Atomization method is a method that is often used to make powders in bulk. Several known atomization methods are the water atomization method, the gas atomization method, and the centrifugal atomization method. Several new methods in the atomization method are the plasma atomization method, liquid explosion atomization method, ultrasonic atomization method, and so on. In this study, molten aluminum metal was used as the starting material, the process used was the oxy-acetylene plasma welding process. The data obtained by testing the distribution of powder, testing the distribution of powder weight, and testing the macro structure of the powder. The powder produced from the oxy-acetylene plasma burst has the characteristics of a non-spherical powder, but is in the shape of a teardrop. This grayish black color is caused by the powder undergoing an oxidation process and a carburizing process. powder weight distribution test, and powder macro structure testing. The powder produced from the oxy-acetylene plasma burst has the characteristics of a non-spherical powder, but is in the shape of a teardrop. This grayish black color is caused by the powder undergoing an oxidation process and a carburizing process. powder weight distribution test, and powder macro structure testing. The powder produced from the oxy-acetylene plasma burst has the characteristics of a non-spherical powder, but is in the shape of a teardrop. This grayish black color is caused by the powder undergoing an oxidation process and a carburizing process.